Effects of acute olanzapine exposure on central insulin-mediated regulation of whole body fuel selection and feeding. (December 2018) - Castellani, Laura N.; Wilkin, Jennifer; Abela, Andrew R.; Benarroch, Louise; Ahasan, Zohra; Teo, Celine; Wilson, Virginia; Kowalchuk, Chantel; Giacca, Adria; Remington, Gary J.; Hahn, Margaret K.
Highlights: Olanzapine increases preference for fatty acid oxidation in light and dark phases. Central insulin decreases food intake and promotes dark phase fatty acid oxidation. Olanzapine suppresses the effects of central insulin on dark phase food intake. Abstract: The use of antipsychotics is associated with severe disruptions in whole body glucose and lipid metabolism which may in part occur through the central nervous system and impaired insulin action at the brain. Here we investigated whether olanzapine treatment might also affect the ability of central insulin treatment to regulate food intake and fuel preference in the light and dark cycle. Male Sprague-Dawley rats were treated with olanzapine (or vehicle solution; 3 mg/kg, subcutaneous) and a simultaneous acute intracerebral ventricular (ICV) infusion of insulin (or vehicle; 3 μL at 10mU; ICV) at the beginning of the 12-h light and dark cycles. Olanzapine treatment reduced RER in the dark and light phases (most consistently in the 4-hours post-treatment), while ICV insulin reduced average RER predominantly in the dark phase, but also at the end of the light cycle. The RER lowering effect of ICV-insulin during the light cycle was absent in the group co-administered olanzapine. The reduction in RER during the dark phase was mirrored by decreased food intake with ICV insulin, but not olanzapine treated rats. The reduction in food intake by ICV-insulin was abolished in rats co-administered olanzapine suggesting rapid induction of central insulin resistance. A combination of ICV-insulin and olanzapine similarly reduced RER in the dark phase, independent of changes in food intake. Olanzapine treatment, alone or in combination with ICV-insulin, significantly reduced VCO2 at regular intervals in the dark phase (specifically 3 h post-treatment), while VO2 was not significantly altered by either treatment. Finally, heat production was increased by olanzapine treatment in the light phase, though this effect was not consistent. The findings confirm that acute olanzapine treatment directly reduces RER and suggest that treatment with this drug may also override central insulin-mediated reductions in food intake at the hypothalamus (while still independently favoring fatty acid oxidation). Acute central insulin similarly reduces RER, but in contrast to olanzapine, this may represent a physiologically appropriate response to reduction in food intake.